Pengolahan Es D’Wecang (Dawet Secang Tapioka) Minuman Tradisonal yang Memiliki Banyak Manfaat - Linda Kusumawati; Yuliarti Rezeki; Wayan Ayu Nastiti; Ariska Dwi Cahyani; Fauziyah Fauziyah (Jurnal Abdimas Adpi Sosial dan Humaniora, 2023)
At this time the life of the Indonesian people has been much influenced by the outside world in terms of lifestyle, clothing, way of speaking, attitude to food and drink. There are lots of foods and drinks from abroad that are popular in Indonesia and there are not a few enthusiasts, from young people, children, to the elderly, and some local foods and drinks are starting to lose interest, even some children don't recognize traditional food and drinks. And Currently, the rise of chemical-based drinks that are not in accordance with human life standards is growing rapidly in Indonesia, along with the development of science and changes in lifestyle, people are becoming more selective and critical of food consumption. to support health. At this PKM we process Dawet Ice made from secang wood and cassava flour which has many health benefits. The PKM method used is environmental reinforcement, Dawet sappan ice processing and marketing strategy. The purpose of this PKM is to preserve local drinks so that they can still exist today. The promotion strategy through social media such as on Instagram, tiktok, through go food, shopee food, and so on will make it easier for us to promote it. Apart from that, we will also continue to innovate so that our products continue to exist and are not out of date. The conclusion is that in this millennial era, we must innovate and take advantage of social media to increase creativity so that products that look simple can have a high selling value, even though they are simple local products, they are still contemporary drinks.